Determination invivo concentration of nanosized drugs to reduce the value of their effective dose - Bondarenko, I. S.; Rakhimova, M. V.; Аврунін, О. Г.; Perekhoda, L. A. (National university of pharmacy, 2020)
These abstracts describe a new acoustomagnetic method for determining the concentration of magnetic nanoparticles, alternative to the method of magnetic resonance imaging. The proposed method for determining the concentration by the acoustomagnetic method can be further used to initiate the release of the drug delivered by magnetic nanoparticles in a constant magnetic field under the action of ultrasound as a result of the manifestation of the nanomechanical mechanism of drug release.
Keywords: acoustomagnetic method; ultrasound; magnetic field; magnetic nanoparticles